2007
DOI: 10.1038/ni1486
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell lineage diversion of T lineage precursors by the essential T cell transcription factor GATA-3

Abstract: GATA-3 is essential for T cell development from the earliest stages. However, highly abundant GATA-3 can drive T-lineage precursors to a non-T fate, depending on Notch signaling and developmental stage. GATA-3 overexpression blocked pro-T cell survival when Notch-Delta signals were present, but enhanced viability in their absence. In double-negative (DN1) and DN2 but not DN3 fetal thymocytes, GATA-3 overexpression rapidly induced mast cell lineage respecification with high frequency by direct transcriptional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
238
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(257 citation statements)
references
References 50 publications
(76 reference statements)
14
238
3
2
Order By: Relevance
“…Both Plzf, a critical factor for iNKT cell function, and Th-POK, a master regulator of CD4 T cell development, are detectable in c-Myc-deficient ST0 and ST1 cells, whereas Gata3 appears slightly elevated. Even small changes in the levels of transcription factors may deregulate networks in control of developmental processes (34). It remains to be determined whether the small transcriptional alterations we observed reflect a significant disturbance in the transcriptional network controlling iNKT cell development.…”
Section: Discussionmentioning
confidence: 90%
“…Both Plzf, a critical factor for iNKT cell function, and Th-POK, a master regulator of CD4 T cell development, are detectable in c-Myc-deficient ST0 and ST1 cells, whereas Gata3 appears slightly elevated. Even small changes in the levels of transcription factors may deregulate networks in control of developmental processes (34). It remains to be determined whether the small transcriptional alterations we observed reflect a significant disturbance in the transcriptional network controlling iNKT cell development.…”
Section: Discussionmentioning
confidence: 90%
“…PU.1, GATA-2, GATA-3, and the microphthalmia-associated transcription factor are essential for mast cell development [22][23][24][25]. We showed that adiposederived CFCs express these four transcription factors as peritoneal cell-derived mast cell controls (Fig.…”
Section: Adipose Tissue Harbors Mast Cell Progenitors and Precursorsmentioning
confidence: 90%
“…CD4 − CD8 − double negative (DN) thymic progenitors consist of DN1 (CD44 + CD25 − ), DN2 (CD44 + CD25 + ), DN3 (CD44 − CD25 + ), and DN4 (CD44 − CD25 − ) populations [6][7]. DN1 and DN2 cells retain both T cell and non-T cell lineage developmental potential [8], whereas final T cell lineage commitment occurs after an irreversible transition from DN2 to DN3 when most T cell-specific genes are upregulated to a peak level [3,5]. Thus, the differentiation of uncommitted thymic progenitors into T cells is a process that can be used to explore the potential relationship between reprogramming factors and differentiation.…”
Section: Introductionmentioning
confidence: 99%